(untitled) (Regional aspects of productive forces development of Ukraine, 2020)
Introduction. Corporate culture serves as a regulator of staff behavior through a system of values, norms, rules established within a single educational institution. Corporate culture can be considered as a kind of management ideology aimed at increasing the business activity of employees, the formation of their corporate identity. Goal is to investigate the phenomenon of corporate culture, to analyze the structure and functions of corporate culture, to characterize the features of the corporate code, to reveal the essence of corporate symbols; to present the main aspects of forming the corporate culture of a higher education institution (on the example of the Western Ukrainian National University). Method. The research methodology is based on the complex application of general scientific methods, including analysis and synthesis. The applied historical and cultural approach involves the study of corporate culture as a socio-cultural phenomenon, its role in creating the image of the university. Results. The scientific novelty of the obtained results is reflected both in the very formulation of the problem and in a comprehensive approach to its solution; The work is a study of the innovative activities of higher education institutions in the formation and development of corporate culture, is a critical analysis of previously unexplored aspects of the Western Ukrainian National University. The results of the study are reflected in the conclusions. Conclusions. It is established that the management of a higher education institution forms a corporate culture, thanks to which employees identify themselves as a professional community that stands out in the market of educational services. The directions of improvement of corporate culture of the university are offered, the basic principles of effective corporate culture, the maintenance of the corporate code, and also a role of corporate symbols in formation of image of university are analyzed.